FAKTOR PENENTU TERBENTUKNYA BUDAYA KERJA INOVATIF (STUDI PADA POLITEKNIK HARAPAN BERSAMA) - Erni Unggul Sedya Utami; Bahri Kamal (Politeknik Ganesha Medan, 2023)
Educational institutions are institutions that provide services to consumers in the form of services, the results of which are not visible, such as manufacturing companies that can produce products that are visible when delivered to the public. Educational institutions in order to keep abreast of changing times, educational institutions are required to innovate. This research was conducted at the Polytechnic Harapan Bersama with a total of 225 respondents. Statistical analysis test performed with the PLS test with a SmartPLS 3.0. The existence of leadership transformation influences innovative work culture successfully mediated in part by work autonomy because without going through work autonomy there. Without going through work autonomy, there is leadership transformation that influences existing innovative culture, astests. Supportive management failed to become a mediating variable because supportive management has no effect on innovative work culture as evidenced by the statistical tests conducted